Climatic impact of lowland deforestation on tropical montane cloud forests in Costa Rica - Nair, Udaysankar S., author; Welch, Ronald, advisor; Pielke, Roger, Sr., advisor; Randall, David, committee member; Vonder Haar, Thomas, committee member; Culver, Roger, committee member (Colorado State University. Libraries, 2002)
Tropical montane cloud forests depend on predictable, frequent, and prolonged immersion in clouds. Recent studies have shown that there has been a reduction in dry season moisture input from direct interception of cloud water and wind blown mist at the lee edge of the Monteverde cloud forest, Costa Rica, since the mid 1970s. This reduction of moisture could be responsible for the population crashes of anurans observed in the region. It has been hypothesized that this behavior is a result of increases in cloud base height, linked to increased sea surface temperatures. This study presents a complementary hypothesis, that deforestation upstream of the Monteverde cloud forest preserve is responsible for the observed changes in cloud base height.

An automated cumulus cloud classification scheme is used to extract monthly spatial maps of the frequency of occurrence of cumulus cloudiness over Costa Rica from GOES- 8 visible channel satellite imagery. It is found that cumulus cloud formations in the morning hours over deforested regions are suppressed compared to forested areas. The degree of suppression appears to be associated with the extent of deforestation. This difference in cioud formation between forested and deforested areas is a clear signal of land-use change influencing the regional climate.

The Regional Atmospheric Modeling System (RAMS) numerical modeling simulations are used to explore the differences in cloud field characteristics over the lowland pasture and forest surfaces. Statistically significant differences in cloud base height and cloud thickness are found between the forest and pasture simulations, clouds having higher base heights and being thinner over pasture surfaces compared to forest surfaces. There are enhanced sensible heat fluxes over pasture surfaces compared to forest surfaces, while forest surfaces have higher latent heat fluxes.

RAMS is also used to examine the impact of lowland deforestation on orographic cloud formation. Numerical modeling simulations of orographic cloud formation is examined for three types of deforestation scenarios, namely forested, completely deforested, and partially deforested where the most recent estimate of forest cover for the Costa Rican region is used. Numerical modeling suggests that deforestation shrinks the areal extent of the orographic cloud banks and elevates its base to higher altitudes. The increase in cloud base height is on the order of 200 m for complete deforestation and 100 m for partial deforestation. Increases in cloud base height of this magnitude may significantly impact the hydrology of the cloud forest regions. Deforestation results in a decrease of the orographic cloud cover, with the decrease being proportional to the amount of deforestation.

The results from this study suggest that land use in tropical lowlands has serious impacts on ecosystems in adjacent mountains. Deforestation in the Costa Rican lowlands may have a detrimental effect of increased frequency of mist free days upstream at Monteverde cloud forest preserve.
Keywords: geophysics